Kolory Afryki w powieści Henryka Sienkiewicza W pustyni i w puszczy. Część II: ludzie i ich wytwory - Borejszo, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The object of studies presented in the article are the designations of colours documented in the novel by Henryk Sienkiewicz entitled In Desert and Wilderness. Against all appearances, it is not the issue treated only marginally by the writer, which may be a little surprising if we take into account the character of the book (an adventure novel for youth, focused basically on the lively, attracting attention plot and not on extensive author’s narration). The author of the article distinguishes more than a dozen of groups of realities especially often characterised from the point of view of their colours. Primarily, these are the descriptions concerning the world of African flora and fauna – exotic for the Polish reader. As it results from the conducted studies, the attention of Sienkiewicz is mainly drawn to the colours of animals, especially birds. It is likely that the writer’s predilection for hunting played here a decisive role. African flora is basically presented in the form of colourful spots against the background of greenery, and not by detailed descriptions of the appearance of individual representatives of a given species. Additionally, the writer’s interest is aroused by changes of colours of the sky and the whole surrounding world depending on the time of day, atmospheric conditions, light intensity (mainly sunrises and sunsets). In the descriptions of people, the narrator pays attention to the differences in the skin colour of the Europeans, Blacks and Arabs. Sienkiewicz devoted less attention to the colours of clothes or ornaments worn by African residents. The lexis used in the novel, belonging to the field of colours, although semantically quite rich and formally varied, is not very original. There dominate here typical adjectival designations used in their basic meanings, instead of inventive comparisons or metaphors, e.g., biały (white), czarny (black), czerwony (red), zielony (green), żółty (yellow), niebieski (blue), różowy (pink), szary (grey), srebrny (silver), złoty (gold). In the studied novel, the field of red has been documented with most examples (e.g., czerwonoskóry (red-skinned), czerwony (red), koralowy (coral), krwawy (bloody), ognisty (fiery), purpurowy (purple), wiśniowy (cherry), zaczerwieniony (reddened); czerwono (red), pąsowo (bright red), wiśniowo (cherry); purpura (purple), rubin (ruby); czerwienić się (to become red), zaczerwienić się (to redden)), and further on: the field of white (for example: białawy (whitish), biały (white), pobladły (pale), śnieżny (snowy), wybielony (whitened), zbielały (bleached); biało (white); pobielenie (whitening); blednąć (to become pale), bielić się (to grow white), pobieleć (to become white), poblednąć (to grow pale), wybieleć (to grow white), zabielić się (to paint white), zblednąć (to turn pale)), the field of blue (for example: błękitnawy (bluish), błękitny (azure), granatowy (navy blue), jasnoniebieski (light blue), niebieski (blue), sinawy (glaucous), siny (livid), siwobłękitny (grey blue); błękitno (blue); błękit (azure); sinieć (to become livid)), the field of green (for example: ciemnozielony (dark green), jasnozielony (bright green), koloru morskiej wody (the colour of sea-water), szarozielony (grey-green), zielonawy (greenish), zielony (green); zielonawo (greeny), zielono (green); zieloność (greenness)), and also the field of black (for example: barwy węgla (the colour of coal), czarny (black), poczerniały (blackened), sczerniały (turned black); czarno (black); czernieć (to grow black), czernić się (to go black), sczernieć (to grow black)), the field of grey (for example: płowoszary (tan-grey), popielaty (ash-coloured), stalowy (steel-like), szary (grey), szyfrowy (slate), zielonoszary (green-grey); poszarzeć (to become grey)), the field of brown (for example: brunatny (tawny), kasztanowy (auburn), opalony (suntanned), rudy (ginger), smagły; opalać się (to bronze), opalić się (to get a suntan)), the field of yellow (for example: cynamonowy (cinnamon), płowożółty (buff-yellow), płowy (buff), woskowy (wax), żółty (yellow)), the field of silver (for example: srebrny (silver), srebrzysty (silvery); srebrno (silver); posrebrzeć (to silver-plate), rozsrebrzyć (to become silvery)), the field of pink (for example: różany, różowy; różowo; różowieć), the field of gold (for example: złoty (golden); złoto (gold); złocić się (to show golden)) and the field of violet (for example: lila (lilac), liliowy (lilac); ametyst (amethyst)). In the field of varied colours we can find, among others, such designations as: pręgowany (striped), pstry (spotted), siedmiobarwny (seven-coloured), różnobarwny (many-coloured), różnokolorowy (colourfull), drgać odblaskami pawich piór (tremble with reflections of peacock feathers), mienić się jak opale (to shimmer like opals), mienić się jak tęcza (to shimmer like a rainbow), mienić się i grać wszelkimi barwami jak wielkie kwiaty (to glitter and play with all colours like huge flowers), przybrać barwę muszli perłowej (to assume the colour of a pearl conch). Among the general descriptions of colours we can enumerate the adjective kolorowy (colourful) and the expression jaskrawo upierzony (brightly feathered), which can signify both mono-, as well as multi- colours of the realities being described. In the studied novel, there are quite numerous examples of words from the field signalling different intensity of light, from full brightness to absolute darkness, for instance: blady (pale), blado (pale), blask (radiance), blednąć (to grow pale), jasny (bright), rozjaśnić (to light up), światło (light), ciemny (dark), ciemno (dark), ciemność/ciemność tak gęsta, że prawie namacalna (darkness/darkness so thick as almost touchable), ćma (moth), mrok (dimness), pociemnieć (to make dark), ściemnić się (to become dark). Two adjectives designating colours manifest the greatest frequency, i.e., biały (white) (106 occurrences in the text) and czarny (black) (58 occurrences), and subsequently – according to the frequency of use – the adjectives: czerwony – red (24), różowy – pink (16), zielony – green (13), żółty – yellow (10), płowy – buff (9), szary – grey (9), srebrny – silver (7), niebieski – blue (6), złoty – gold (6), białawy – whitish (5), błękitny – blue (5), purpurowy – purple (5), popielaty – ash-coloured (4). Additionally, attention should be brought to the designations of colours in less typical forms, e.g., comparisons, metonymy, metaphor. Among the comparative expressions we can find the designations frequently used in Polish, such as: biały jak kreda/mleko/papier/śnieg (as white as chalk/milk/paper/snow), czarny jak aksamit/kir/noc (as black as velvet/pall/night ), czarno jak w piwnicy (as black as in the cellar), czerwony jak krew (as red as blood), szary jak mysz (as grey as a mouse). Among the designations of colours which are less typical than the ones mentioned above there are collocations such as: drgać odblaskami pawich piór (tremble with reflections of peacock feathers), mieć barwę czystego ametystu (to have the colour of pure amethist), przybrać barwę muszli perłowej (to assume the colour of a pearl conch), mienić się jak opale (to shimmer like opals), mienić się jak tęcza (to shimmer like a rainbow). There is definitely more information about the colours of the world depicted in the studied novel by Sienkiewicz than in The Trilogy written by the same author, especially when we take into account the differences in length of the analysed writings. In the novel In Desert and Wilderness there dominate the descriptions of colours of nature—which is exotic for Polish readers—rather than people, which results, among others, in greater frequency of designations from the colour field ascribed to African flora (green and pink) if we compare it with The Trilogy.